Membangun Komitmen Berwirausaha Melalui Motivasi Berwirausaha dan Kepuasan Kerja Pada Industri Kecil Menengah (IKM) - Aditya, Rini Pradina; Abadiyah, Rifdah; Ubaidillah, Hasan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The goal of this research was to better comprehend the impact of leadership style, entrepreneurial drive, and job satisfaction on employee dedication to the workplace. The quantitative methodology used in this study allows for detailed descriptive analysis. A lengthy questionnaire with several statements and assessments on a Likert Scale was used to compile the data for this study. One hundred people took part in this research since they were chosen at random. The analysis procedure often involves the use of SPSS, a statistical tool. Leadership style was shown to positively correlate with all measures of work satisfaction, as well as with measures of entrepreneurial commitment, job satisfaction, and entrepreneurial motivation.